2008
DOI: 10.5694/j.1326-5377.2008.tb02024.x
|View full text |Cite|
|
Sign up to set email alerts
|

Does practice make perfect? The effect of coaching and retesting on selection tests used for admission to an Australian medical school

Abstract: Objective: To assess the practice effects from coaching on the Undergraduate Medicine and Health Sciences Admission Test (UMAT), and the effect of both coaching and repeat testing on the Multiple Mini Interview (MMI). Design, setting and participants: Observational study based on a self‐report survey of a cohort of 287 applicants for entry in 2008 to the new School of Medicine at the University of Western Sydney. Participants were asked about whether they had attended UMAT coaching or previous medical school i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 11 publications
4
56
0
2
Order By: Relevance
“…We have not been able to measure such potential influences in this study. However, Griffin et al [15], in a study of 287 applicants to the School of Medicine at the University of Western Sydney, reported that in the 51.4% of the cohort who had prior UMAT coaching, there was no coaching effect on UMAT-1 and UMAT-2. However, there was evidence of a small coaching effect on UMAT-3 (approximately 3.8% increase in score).…”
Section: Discussionmentioning
confidence: 99%
“…We have not been able to measure such potential influences in this study. However, Griffin et al [15], in a study of 287 applicants to the School of Medicine at the University of Western Sydney, reported that in the 51.4% of the cohort who had prior UMAT coaching, there was no coaching effect on UMAT-1 and UMAT-2. However, there was evidence of a small coaching effect on UMAT-3 (approximately 3.8% increase in score).…”
Section: Discussionmentioning
confidence: 99%
“…Their results correspond with the difficulties outlined in our study such as cost and perceived level of difficulty but only included those who had been successful in the medical school selection process. One small Australian study of 287 applicants assessed the impact of coaching on the UMAT and coaching and repeat testing on the MMI [21]. They found that coaching had a small effect on the parts of the UMAT test but was ineffective in improving the scores of the MMI.…”
Section: Discussionmentioning
confidence: 99%
“…There is little research regarding the lengths applicants go to in order to maximise their chance of receiving an offer or the difficulties they encounter during this process [21-23]. Moreover, there is little evidence on of the impact of the preparatory activities undertaken or difficulties encountered on the outcome [24].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were also concerned that coaching could improve performance presenting an additional barrier to applicants from lower socio-economic groups. There is evidence that coaching improves performance on Section 3 of both HPAT-Ireland (O'Flynn et al 2012) and UMAT (Griffin et al 2008(Griffin et al , 2012. Hence there is a strong argument for removing this section entirely from the paper.…”
Section: Discussionmentioning
confidence: 99%